Morpho-Anatomical Analysis of Cosmostigma racemosum (Asclepiadoideae) Flowers - Widodo Widodo; Mohamad Amin; Mimien Henie Irawati Al-Muhdar; Muhammad Ja’far Luthfi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2014)
Cosmostigma racemosum is a plant species belonging to the family Apocynaceae, the subfamily Asclepiadoideae. Cosmostigma racemosum is found in Nglanggeran Mountain Gunungkidul, Yogyakarta. The local name and its original distribution are not known. Information or study of Cosmostigma racemosum in Indonesia is not available. Comprehensive characterization of this species is important for authentication and addition of data base. Characterization was conducted by analyzing the morphology and anatomy of flower. The objectives of this study were to describe and analyze the morphology and anatomy of C. racemosum flowers. The method of research was based on observation method and exploration of plant systematics evidence or taxonomy evidence, including analyses and description of morphology and anatomy of flower structure and its development. The results showed that the characteristics of flower morphology are in accordance with the existing description in literatures. Characteristics of pollinia are specific characters of morphological aspect of flower. Data of anatomy of flower and its parts development are the new ones which confirm the position of C.racemosum as a member of the tribe Marsdenieae. The data of anatomy also show new information of the ontogeny of the important parts of flower: pollinia formation, pollinia corpusculum, anther wall, anther sac, stigma, stamen, staminal tube, stigmatic chamber, and structure of ovary in Asclepiadoideae